PENDIDIKAN KARAKTER MELALUI KEGIATAN ESKTRAKULIKULER KARATE PADA SISWA SMP NEGERI 2 KOTA KUPANG - Paulinus Danggur; Jusuf Blegur; Julian J Leko (Nusa Cendana University, 2020)
The data are obtained from primary data and secondary data. Primary data collection methods obtained from interviews, observations and main documents. Meanwhile, secondary data comes from interviews, library data, books and other literature as a complement to primary data. In this study, the data collection techniques used were: observation, interview and documentation. While the data analysis method uses descriptive analysis. The findings of the study indicate that character education through extracurricular karate activities in students of SMPN 2 Kupang City by examining each movement and exemplary method. This implementation has a positive impact on students. Whether in terms of honesty, responsibility, discipline, religion, independence, tolerance, hard work spirit, curiosity, environmental care, friendly, democratic, creative, peace-loving. The implementation of character education in extracurricular activities will not be carried out well, of course there are several supporting factors, one of which is a coach who is able to insert material character values ​​contained in every movement. The conclusion from the results of the data analysis is that the examination of research results and discussion can be concluded that: Character Education through Extracurricular Karate Activities in Students of SMPN 2 Kupang City is in the good category.